2010
DOI: 10.1039/c0dt00813c
|View full text |Cite
|
Sign up to set email alerts
|

The complexation of rhodium(iii) with acyclic diaminedithioether (DADTE) ligands

Abstract: (103)Rhodium(III) complexes derived from seven acyclic tetradentate N(2)S(2) ligands (one diaminedithiol and six diaminedithioether ligands) have been synthesized and characterized. Structural variations in the ligand include the length of carbon backbone between the coordinating atoms (222; 232; 323; 333), the presence or absence of gem-dimethyl groups α to sulfur, and the nature of the organic moiety on the sulfurs (hydrogen, p-methoxybenzyl and methyl). For each ligand, the formation of cis and/or trans dic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 17 publications
0
6
0
Order By: Relevance
“…A series of acyclic S 4 ligands were evaluated by Goswami et al, who found that these ligands could be labeled in >90% yield by heating at 85 °C at pH 4–5 for 60 min. , As is the case with other 105 Rh labeling reactions, ethanol is an essential component of the reaction mixture, presumably reducing the Rh­(III) starting material to more labile Rh­(I). Akgun et al subsequently investigated a series of acyclic amine-thioether ligands and found that the complexation yields were lower than with the tetrathioethers (45–60% vs >90%), presumably because the lower labeling pH was suboptimal for the amine moieties . An additional complication with this class of ligands is the formation of conformers (Figure ).…”
Section: Rhodiummentioning
confidence: 99%
See 1 more Smart Citation
“…A series of acyclic S 4 ligands were evaluated by Goswami et al, who found that these ligands could be labeled in >90% yield by heating at 85 °C at pH 4–5 for 60 min. , As is the case with other 105 Rh labeling reactions, ethanol is an essential component of the reaction mixture, presumably reducing the Rh­(III) starting material to more labile Rh­(I). Akgun et al subsequently investigated a series of acyclic amine-thioether ligands and found that the complexation yields were lower than with the tetrathioethers (45–60% vs >90%), presumably because the lower labeling pH was suboptimal for the amine moieties . An additional complication with this class of ligands is the formation of conformers (Figure ).…”
Section: Rhodiummentioning
confidence: 99%
“…Akgun et al subsequently investigated a series of acyclic amine-thioether ligands and found that the complexation yields were lower than with the tetrathioethers (45−60% vs >90%), presumably because the lower labeling pH was suboptimal for the amine moieties. 214 An additional complication with this class of ligands is the formation of conformers (Figure 9). In later studies, the amine-thioether ligands were supplanted by diaminediphosphine and dithiodiphosphines, which facilitate complexation at lower temperatures and lower ethanol concentrations because the phosphines act as reductants.…”
Section: Chemistrymentioning
confidence: 99%
“…30 Acyclic diamine dithioether chelates of varying backbone length were evaluated for complexation with Rh(III) and found to result in the presence of multiple isomers. 31 Substitution reactions on the Rh(III) center require in situ reduction to Rh(I) for facile ligand exchange followed by air oxidation to yield the desired Rh(III) complex. 32 At the radiotracer level, refluxing ethanol has been used for this purpose.…”
Section: Rhodium-105mentioning
confidence: 99%
“…A pentadentate N 3 S 2 bicyclic macrocyclic ligand, 4,10-dithia-1,7,13-triazabicyclo[11.3.3]nonadecane, was found to complex 105 Rh in greater than 98% yield at pH 5 and 80 °C for 1 h. The X-ray crystal structure of the nonradioactive analog showed the Rh(III) complex to have the form [RhCl(N 3 S 2 )]Cl 2 , with the secondary amine trans to the chloride ligand . Acyclic diamine dithioether chelates of varying backbone length were evaluated for complexation with Rh(III) and found to result in the presence of multiple isomers …”
Section: Radionuclides For Imaging and Therapymentioning
confidence: 99%
“…Rhodium-105 (β - , 100%, half-life 1.47 days) is a beta-emitter with potential applications in radionuclide therapy. Various bifunctional chelator systems based on combinations of soft donor groups (amine, thioether and phosphine) have been evaluated with some promise but have not yet translated into therapeutic evaluation 7173…”
Section: Groupmentioning
confidence: 99%